2022
DOI: 10.1021/acs.est.1c08502
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Oxidizing Capacity of the Periodate–H2O2 Mixture: Identification of the Primary Oxidants and Their Formation Mechanisms

Abstract: This study reexamined the mechanisms for oxidative organic degradation by the binary mixture of periodate and H2O2 (PI/H2O2) that was recently identified as a new advanced oxidation process. Our findings conflicted with the previous claims that (i) hydroxyl radical (•OH) and singlet oxygen (1O2) contributed as the primary oxidants, and (ii) •OH production resulted from H2O2 reduction by superoxide radical anion (O2 •–). PI/H2O2 exhibited substantial oxidizing capacity at pH < 5, decomposing organics predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…Hydrogen peroxide (H 2 O 2 ) is an important reactive oxidant in aquatic redox processes and holds a unique position in aquatic environments, affecting the speciation and biogeochemistry of transition metals , as well as contributing to the degradation of natural and anthropogenic organic compounds. H 2 O 2 is ubiquitously detected in various water environments, including freshwater, rainwater, estuarine, and marine environments, at concentrations varying from 0.01 to 30 μM. Generally, the formation of H 2 O 2 in sunlit surface water is primarily from the dismutation of superoxide radicals (HO 2 · /O 2 · – ), which are produced by one-electron reduction of dioxygen. , Meanwhile, previous studies reported that the addition of external phenols would enhance the photoproduction of H 2 O 2 because the presence of external phenols as electron donors essentially promoted the photoproduction rate of O 2 · – . It is commonly accepted that the fate of H 2 O 2 is to generate a hydroxyl radical ( · OH), which is also critical in aquatic environments as a nonselective oxidant. The formation of · OH from H 2 O 2 induced by transition metal catalysis (Fenton and Fenton-like reactions) or UV-irradiation is well known and has been extensively investigated. However, the investigation of metal-independent and UV-light free production of · OH from H 2 O 2 to date is insufficient. Consequently, the detailed transformation mechanism of H 2 O 2 in aquatic environments is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is an important reactive oxidant in aquatic redox processes and holds a unique position in aquatic environments, affecting the speciation and biogeochemistry of transition metals , as well as contributing to the degradation of natural and anthropogenic organic compounds. H 2 O 2 is ubiquitously detected in various water environments, including freshwater, rainwater, estuarine, and marine environments, at concentrations varying from 0.01 to 30 μM. Generally, the formation of H 2 O 2 in sunlit surface water is primarily from the dismutation of superoxide radicals (HO 2 · /O 2 · – ), which are produced by one-electron reduction of dioxygen. , Meanwhile, previous studies reported that the addition of external phenols would enhance the photoproduction of H 2 O 2 because the presence of external phenols as electron donors essentially promoted the photoproduction rate of O 2 · – . It is commonly accepted that the fate of H 2 O 2 is to generate a hydroxyl radical ( · OH), which is also critical in aquatic environments as a nonselective oxidant. The formation of · OH from H 2 O 2 induced by transition metal catalysis (Fenton and Fenton-like reactions) or UV-irradiation is well known and has been extensively investigated. However, the investigation of metal-independent and UV-light free production of · OH from H 2 O 2 to date is insufficient. Consequently, the detailed transformation mechanism of H 2 O 2 in aquatic environments is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…− was the major species of periodate at pH < 8.0, [2][3][4]7,10,12 the predominance of IO 4 − was not clearly evidenced. 18 Instead, several lines of evidence have revealed that the periodate species are more likely present as H 4 IO 6 − and H 3 IO 6 − under acidic and neutral conditions, wherein IO 4…”
Section: •−mentioning
confidence: 84%
“…21 On the contrary, in periodate-based AOPs, the change of periodate speciation was often overlooked, and only a few studies have tried to elucidate its potential effects on organic contaminant degradation. 4,10,12 − was also considered to be the dominant periodate species at pH < 8, which could transform into less-reactive H 2 I 2 O 10 4− species at high pH levels. Although the abovementioned studies and many other studies supposed that IO 4…”
Section: •−mentioning
confidence: 99%
See 2 more Smart Citations